Significant breast injury after road traffic collision. (January 2014) - Pressney, I; Stedman, B; King, LJ
There are many causes for uncontrolled haemorrhage in a restrained person involved in a road traffic collision requiring resuscitation and further intervention. A rare cause of significant bleeding can result from breast trauma. Breast injury as part of the spectrum of the 'seat belt syndrome' has been classified based on review of previously reported cases ranging from mild class I crush injuries through to severe avulsion class IV injuries. In the documented literature there are few reports of the more severe class IV injuries for which we present a case of significant bleeding into the breast with prompt endovascular intervention to arrest the haemorrhage.